A brief review on supercapacitor energy storage devices and utilization of natural carbon resources as their electrode materials. (15th December 2020) - Saikia, Binoy K.; Benoy, Santhi Maria; Bora, Mousumi; Tamuly, Joyshil; Pandey, Mayank; Bhattacharya, Dhurbajyoti
Graphical abstract: Highlights: The status on the natural carbon sources used in supercapacitor electrode is compiled. Technological advances in supercapacitor fabrication are discussed. The advancement in different constituents of supercapacitors is critically reviewed. Abstract: Affordable and clean energy is one of the major sustainable development goals that can transform our world. Currently, researchers are focusing on cheap carbon electrode materials to develop energy storage devices, including high energy density supercapacitors and Li-ion batteries. In this review article, the prime focus has been given on different types of natural carbon sources used for synthesis of graphene and carbon products/derivatives towards the fabrication of supercapacitors with high electrochemical performance. The review also contains the recent status of the synthetic methods of such type of materials and their subsequent application as electrodes in supercapacitors along with the technological aspects of the supercapacitors made out of those natural resources. The main outlook of the review article is to understand the importance of these natural resources for using as precursors in large-scale synthesis of various carbon products/derivatives in an economic way. This is the first review article describing all possible directions related to such typical natural resources and application of their carbon derivatives/products for better electrochemical properties. The article will be very helpful for future research work in the field of carbon electrode materials derived from coal, graphite, and biomass and their gainful utilization in supercapacitor energy storage devices.